Specific features of pathology of gastro-duodenal zone organs in children of preschool and junior school age - Ilona Bulich; Oksana Tsiura; Nataliya Shevchenko; Ladzekpo Joyce Amegah; Osaloni Sarah Omonor (Актуальні проблеми сучасної медицини, 2021)
Pathology of organs of gastrointestinal tract - one of constituents of serious problem of health of child's population, that has certain features in the different age-related groups. The aim of this study was to analyse structure and features of pathology of organs of gastro-duodenal zone for the children of preschool and junior school age in the conditions of work of general somatic permanent establishment. Materials and methods. The results of child's gastroenterologist’s and endoscopist’s cabinet’ work at the SI “Institute of children and adolescences health care of National Academy of Medical Science” of Kharkiv were analysed for the last five years. 107 children were inspected in age from 5 to 10 years for this time. Upper endoscopy and intragastric pH-metry were conducted to all children. Results. Peculiarities of the clinical picture in children were the presence of abdominal pain of moderate intensity with localization in the epigastric region. When analyzing the nature of sex-dependent pain, it was found that early pain was predominant in boys, while late pain was more common in girls. Of the dyspeptic complaints, nausea was the most frequent, with 37.4 ± 4.6% of children complaining. When analyzing the endoscopic picture, it should be noted that pathological changes were more often registered in the age group of 8-10 years. When performing intragastric pH-metry hyperacidity was detected 2 times more often than normoacidity. Functional disorders of the gastrointestinal tract predominated in preschool children. According to the results of ultrasound of the gallbladder, the presence of gallbladder inflection was found in almost all subjects, and also more than half of this inflection was combined with bladder enlargement. Conclusions: 1. the children of preschool age have atrophic and destructive forms of defeat of mucous membrane of stomach and duodenum considerably rarer; 2. for children 7-8 years old, mainly children who study at school first year, more often there are agile violations, atrophic and destructive forms of defeat of mucous membrane of stomach and duodenum, that, probably, it is related to influence of stress factor; 3. children of preschool and junior school age have the united character of motion, that it is important to take into account at the choice of further tactics of conduct and treatment of patient.